Türk Sanat Müzikleri ve Türk Halk Müzikleri Dikotomisinde Önemli Bir Dinamik: “Toplumsal Katmanlar” / The Dichotomy between Art Music and Folk Music in the Framework of Turkish Traditional Music and its Relation with Social Layers - Ersoy, İlhan (Journal of History Culture and Art Research, 2018)
Abstract This article examines the diversity in music with a “sociological/social” centered perspective. Based on the fact that music has a social basis independent of all other musical components, the article asserts that different societies have different kinds of music at both the national and international scale. In other words, the differentiation of societies also differs the music they produce and consume. This approach theoretically carries the subject over to the grounds of ethnomusicology which is a musical discipline that leans against anthropology. The article first examines the relationship between music-society providing examples regarding the fact that there is a differentiation in music just as societies are separated into different layers. Afterwards, the relationships of Turkish Art Music and Turkish Folk Music with different social layers at different geographies are taken into consideration. Secondly, the article also carries out evaluations on the differentiation of Turkish Art Music and Turkish Folk Music on a social basis as two different musical traditions of Turkey. It has been put forth through various examples in the article that Turkish Art Music is a music type that has developed under the auspices of the ruling class. Whereas Turkish Folk Music has not received sufficient attention from the ruling class even if it has been supported from time to time. In addition, it has been argued that Turkish Folk Music is a type of music that contains different cultures and local traces instead of being the only type of music adopted by the public. The cultural context of music has been examined in the final section of the article thereby making evaluations by way of concepts such as public culture, learned culture and hybrid culture. Öz Bu makale, müzikteki çeşitliliği, “sosyolojik/toplumsal” merkezli bir bakış açısıyla incelemektedir. Yani makale, var olan diğer müziksel bileşenlerden bağımsız bir biçimde, müziklerin toplumsal bir zemini olduğundan hareket ederek hem ulusal hem de uluslararası ölçekte, farklı toplumların farklı müziklere sahip olduğunu savunmaktadır. Bir başka ifadeyle, toplumların farklılaşması, onların ürettikleri ve tükettikleri müzikleri de farklılaştırır. Bu yaklaşım, konuyu kuramsal olarak, antropolojiye yaslanan müziksel bir disiplin olan, etnomüzikoloji zeminine de taşımaktadır. Makalede öncelikle müzik-toplum ilişkisi incelenerek toplumların farklı tabakalara ayrılması gibi müzikte de bir farklılaşmanın olduğu konusunda örnekler sunulmaktadır. Sonrasında ise Türk Sanat Müziği ve Türk Halk Müziği türlerinin farklı coğrafyalarda farklı toplumsal katmanlar ile ilişkisi ele alınmaktadır. Makale ikinci olarak, Türkiye’deki iki farklı müzik geleneği olan Türk Sanat Müziği ve Türk Halk Müziği türlerinin toplumsal zemindeki farklılıkları üzerine değerlendirmeler yapmaktadır. Makalede, Türk Sanat Müziğinin yönetici sınıfın himayesinde gelişen bir müzik türü olduğu ile ilgili örneklere yer verilmiştir. Türk Halk Müziği ise zaman zaman yönetici sınıf tarafından desteklense de bu kesimden yeterli ilgiyi görememiştir. Buna ilaveten, Türk Halk Müziğinin halkın bütünü tarafından benimsenen tek bir müzik türü olmak yerine farklı kültürleri içerisinde barındıran ve yöresel izler taşıyan bir tür olduğu savunulmuştur. Makalenin son bölümünde ise müziğin kültürel bağlamı incelenerek halk kültürü, öğrenilmiş kültür ve melez kültür gibi kavramlar üzerinden değerlendirmeler yapılmıştır.